2015
DOI: 10.1186/s11671-015-0878-3
|View full text |Cite
|
Sign up to set email alerts
|

Thermal analysis of Al + 0.1% CNT ribbon

Abstract: The objective of this work is a dilatometric study of Al + 0.1% of multiwall carbon nanotubes nanocomposite material (NCM) in three directions: X - parallel to the rolling direction; Y - perpendicular to the rolling direction and (Z) perpendicular to the ribbon plane. NCM specimens were made in the form of a 0.1-mm-thick ribbon. The temperature range used for measurements was 20°C to 600°C. The obtained results show that presence of nanotubes affects the thermal expansion coefficient (TEC) measured in differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…In addition, thermally activated formation of allotropes over long temperature ranges which might chemically affect the thermal degradation of UFC, is unknown for aluminum in the literature. Similar thermal analysis results of pure aluminum powder have previously been reported …”
Section: Resultssupporting
confidence: 90%
“…In addition, thermally activated formation of allotropes over long temperature ranges which might chemically affect the thermal degradation of UFC, is unknown for aluminum in the literature. Similar thermal analysis results of pure aluminum powder have previously been reported …”
Section: Resultssupporting
confidence: 90%
“…The low-density polyethylene (LDPE) manufactured by “UfaOrgSynthesis” (Russia) with 918.5 ± 1.5 kg/m 3 density and multi-walled carbon nanotubes (MWCNTs) were used for the sample preparation. The nanotubes were made by the CVD method in a rotating reactor [ 9 ]. Powder of the Al 2 O 3 –MoO 3 –Fe 2 O 3 mixture was applied as catalyst.…”
Section: Methodsmentioning
confidence: 99%
“…The results taken by their authors relate to various physical quantities. The researchers independently reached the conclusion that CNTs introduced into various materials result in the improvement of the physico-chemical and thermodynamic properties of the made composites [ 8 , 9 ], e.g., reinforcing polymers with nanotubes considerably alters their thermal and thermomechanical properties [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The published literature about nanomaterials is unanimous in hailing the performance and the positive role of CNTs in polymer or metallic matrices [1, 2]. …”
Section: Introductionmentioning
confidence: 99%
“…Recent studies in Refs. [1, 2] have demonstrated that the introduction of CNTs into polymer or metal matrices causes a decrease in thermal expansion and anisotropy.…”
Section: Introductionmentioning
confidence: 99%